O mapeamento tecnológico e a gestão de tecnologia no CNPDIA - Embrapa - Franco, Renato Ribeiro (2009)
The technology forecast and management methods have been considered by academics and managers important tools to support technology development. Generally the organizations, which are worried about this issues, needs data and information to look ahead and clarify technologies course before it happens. Considering that development s time has become shorter, these kind of methodologies may turn more and more important. Despite of these matters, it s rare to find papers and related cases to this subject in Brazil. That s why this study has the objective of collect and discuss methodologies, and right after that, compare the Technology Roadmap (TRM) to the CNPDIA s method of technology forecast and management. This TRM method is frequently presented in the related magazines. The work realized has compared the dimension of the TRM, considering some extras observations. These extras looks offered a more complete view and understanding of the environment in which the technology activities took place. The expected intention was to collaborate by analyzing some of the CNPDIA s characterizes. One extra hope is to inspire some discussion in the unit observed, based on this work.